High serum alpha‐fetoprotein levels in primary infertile men. (2nd October 2022) - Corsini, Christian; Fallara, Giuseppe; Candela, Luigi; Raffo, Massimiliano; Pozzi, Edoardo; Belladelli, Federico; Capogrosso, Paolo; Boeri, Luca; Costa, Antonio; Schifano, Nicolò; Cignoli, Daniele; Ventimiglia, Eugenio; et al.
Abstract: Background: Alfa‐fetoprotein (AFP) is a serum glycoprotein highly produced during fetal development. While AFP synthesis drops dramatically after birth, AFP production only persists or returns under specific pathological condition. Objective: We sought to investigate the rate of and the potential meaning of high AFP serum levels in men seeking first medical attention for couple's primary infertility. Materials and methods: Socio‐demographic and clinical data from 1803 non‐Finnish, White‐European primary infertile men were retrospectively analysed. AFP was routinely measured in each patient (high AFP was defined as >7 ng/ml). Men with history of liver diseases, testicular cancer, or other known causes of increased AFP levels were excluded from the final analysis. Semen analyses were based on the 2010 World Health Organization reference criteria. Descriptive statistics and logistic regression models tested the association between serum AFP and clinical variables. Possible nonlinear relationships were graphically explored with locally estimated scatterplot smoothing method. Results: Overall, high serum AFP level was found in 29 (1.7%) patients. Normal versus high AFP levels patients were comparable in terms of body mass index (BMI), Charlson Comorbidity Index, waist circumference, smoking habits, history of cryptorchidism, testicular volume, and serum hormones (i.e., follicle‐stimulating hormone, luteinizing hormone, and total testosterone). Conversely, men with higher AFP levels were older ( p  = 0.02), had lower sperm concentration ( p  = 0.003), and were more frequently oligozoospermic and azoospermic (all p  ≤ 0.03). At multivariate analysis, high AFP levels were independently associated with oligozoospermia (OR 3.79; p  = 0.033) and azoospermia (OR 3.29; p  = 0.006). Likewise, if AFP levels increase, patients were found to be older, with higher BMI and to have more comorbidities (all p  < 0.05). Discussion: Unexplained high AFP levels account for almost 2% of cases in primary infertile patients without a previous history of associated disorders. Higher serum AFP levels are linked with aberrant sperm counts, older age, obesity, and a greater amount of comorbid conditions. Conclusion: Despite the need for additional validation, these data suggest that serum AFP measurement might have a multifaceted role over the diagnostic work‐up of males presenting for couple's infertility.